1990
DOI: 10.1590/s0074-02761990000200013
|View full text |Cite
|
Sign up to set email alerts
|

The surface charge of trypanosomatids of the genus trypanosoma

Abstract: Cell electrophoresis was used for determionation of the electrophoretic mobility (EPM) of epimastigo and trypamastigote forms of several isolates of Trypanosoma cruzi and some stocks of other members of the Schizotrypanum subgenus, such as T. dionisii, T. vespertilionis and T. myoti. The EPM of T. bruceli, T. rangeli, and T. conorhini was also determined. The results obtained show that the EPM values con be useful to distinguish the parasites

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Although we were yet to determine which kind of endocytosis was responsible for the uptake of the cationic bacteriocin AS-48, it was tempting to think that it could take place once it had interacted with anionic residues on the outer surface of the parasite ( Souto-Padrón et al, 1990 ), as suggested for the neuropeptide VIP, another cationic trypanocidal peptide believed to bind to negatively charged glycoproteins such as VSG ( Gonzalez-Rey et al, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although we were yet to determine which kind of endocytosis was responsible for the uptake of the cationic bacteriocin AS-48, it was tempting to think that it could take place once it had interacted with anionic residues on the outer surface of the parasite ( Souto-Padrón et al, 1990 ), as suggested for the neuropeptide VIP, another cationic trypanocidal peptide believed to bind to negatively charged glycoproteins such as VSG ( Gonzalez-Rey et al, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of these two subpopulations suggests the presence of distinct evolutive forms in the same sample. It is important to notice that transitional forms, characterized by the presence of a rod-shaped kinetoplast located at the nuclear side and which display some surface characteristics of trypomastigotes, such as the same mean electrophoretic mobility (Souto-Padrón et al 1990a), are frequently found free in the culture medium in variable amounts even when Dm28c parasites are maintained in LIT medium. No data are known about the behavior of transitional forms which incubated in the presence of lectins.…”
Section: Pna-binding Sitesmentioning
confidence: 99%
“…In the case of parasites obtained from axenic media, it has been shown that growth conditions interfere with cell surface composition, as evaluated in studies of parasite-host cell interaction (Araújo-Jorge 1989) and cell agglutination using lectins (Pereira et al 1980;Andrade et al 1991), although they do not interfere with the cell surface charge (Souto-Padrón et al 1984, 1990aDe Souza 1985, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Uma notável característica do T. cruzi é sua heterogeneidade biológica e bioquímica. Os parasitas apresentam diferenças notáveis no seu crescimento, tropismo tissular, composição antigênica e virulência, bem como uma diferente susceptibilidade à quimioterapia e na sua resistência a alguns dos mecanismos da resposta imune (ALCANTARA;BRENER, 1978;SOUTO-PADRON et al, 1990;MARTINEZ-DIAZ;ESARIO et al;2001;CORTEZ et al, 2006).…”
Section: O Parasita E Os Modelos Murinos De Infecçãounclassified